Can intubation confirmed by capnography be misleading? Complication with rabbit intubation. Issue 2 (20th April 2020) - Calice, Ivana; Rocchi, Attilio
Abstract : Rapid and accurate tracheal intubation in rabbits is challenging. It requires skill and is a technically demanding procedure. Visualisation of a normal capnography trace is widely considered the most objective indication of a correct orotracheal intubation, especially with blind intubation and small tidal volumes. This case report describes how a large defect in the oesophageally dislocated endotracheal tube led to misleading positive capnography signal.